2014
DOI: 10.11131/2014/101094
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of TPR-Domain Immunophilins in the Mechanism of Action of Steroid Receptors

Abstract: Abstract. In the absence of ligand, some members of nuclear receptor family such as corticosteroid receptors are primarily located in the cytoplasm, and they rapidly accumulate in the nucleus upon ligand-binding. Other members of the family such as the estrogen receptor are mostly nuclear. Regardless of their primary location, these oligomeric proteins undergo a dynamic nuclearcytoplasmic shuttling, and their transport through the cytoplasmic compartment has always been assumed to occur in a stochastic manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 182 publications
(216 reference statements)
0
6
0
Order By: Relevance
“…Upon steroid binding, they rapidly accumulate in the nucleus. Other receptors such as the estrogen receptor (ER) are constitutively nuclear even in the absence of steroid, but they are not statically confined to a cell compartment, but are continuously shuttling between cytoplasm and nucleus [44,45,46,47]. Classically, the driving force for soluble protein movement throughout the cytoplasm was always assumed to occur by simple diffusion, and steroid receptors were not the exception.…”
Section: Immunophilins Play a Key Role In Protein Traffickingmentioning
confidence: 99%
“…Upon steroid binding, they rapidly accumulate in the nucleus. Other receptors such as the estrogen receptor (ER) are constitutively nuclear even in the absence of steroid, but they are not statically confined to a cell compartment, but are continuously shuttling between cytoplasm and nucleus [44,45,46,47]. Classically, the driving force for soluble protein movement throughout the cytoplasm was always assumed to occur by simple diffusion, and steroid receptors were not the exception.…”
Section: Immunophilins Play a Key Role In Protein Traffickingmentioning
confidence: 99%
“…In previous studies, we demonstrated that TPR-domain immunophilins affect the subcellular localization of steroid receptors (Galigniana, 2012;Galigniana et al, 2010bGaligniana et al, , 2001Mazaira et al, 2014). Thus, it was shown that FKBP52 is required for the nuclear accumulation of the receptor thanks to a dynein-dependent cytoplasmic mechanism, whereas FKBP51 increases the cytoplasmic pool of the receptor and decreases its nuclear pool.…”
Section: Discussionmentioning
confidence: 95%
“…). Because the PPIase domain of FKBP52, but not the PPIase domain of FKBP51, is able to interact with dynein/dynactin, the motor protein complex is also recruited to steroid receptors and powers the active cytoplasmic transport to the nucleus along cytoskeletal tracks …”
Section: Hsp90‐binding Immunophilins and Transcription Factorsmentioning
confidence: 99%
“…In nontransformed isoforms, the stoichiometry of the receptor•(Hsp90) 2 complex shows one molecule of Hsp70, one molecule of p23 and a TPRdomain cochaperone bound to the TPR acceptor site of the Hsp90 dimer. 12,13 During the early steps of heterocomplex assembly, the TPR protein Hop/p60/Sti1 is required for bringing together Hsp90 and Hsp70, but after the formation of the complex and its subsequent transference to the aporeceptor, Hop/p60/Sti1 is released and a TPR-domain immunophilin occupies the TPR acceptor site on the Hsp90 dimer. FKBP51 is the immunophilin present in the mature and transcriptionally inactive receptor and is exchanged by FKBP52 upon steroid binding ( Fig.…”
Section: Hsp90-binding Immunophilins and Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation